2- and 3-Fluoro-3-deazaneplanocins, 2-fluoro-3-deazaaristeromycins, and 3-methyl-3-deazaneplanocin: Synthesis and antiviral properties. Issue 17 (1st September 2015) - Liu, Chong; Chen, Qi; Gorden, John D.; Schneller, Stewart W.
Graphical abstract: Abstract: The 3-deaza analogs of the naturally occurring adenine-based carbocyclic nucleosides aristeromycin and neplanocin possess biological properties that have not been optimized. In that direction, this paper reports the strategic placement of a fluorine atom at the C-2 and C-3 positions and a methyl at the C-3 site of the 3-deazaadenine ring of the aforementioned compounds. The synthesis and S -adenosylhomocysteine hydrolase inhibitory and antiviral properties of these targets are described. Some, but not all, compounds in this series showed significant activity toward herpes, arena, bunya, flavi, and orthomyxoviruses.